Predicting potential distribution of Ziziphus spinosa (Bunge) H.H. Hu ex F.H. Chen in China under climate change scenarios - Qian Zhao; Ze‐Yuan Mi; Chan Lu; Xin‐Fei Zhang; Li‐Jun Chen; Shi‐Qiang Wang; Jun‐Feng Niu; Zhe‐Zhi Wang (Ecology and Evolution, 2022)
Abstract Ziziphus spinosa (Bunge) H.H. Hu ex F.H. Chen is a woody plant species of the family Rhamnaceae (order Rhamnales) that possesses high nutritional and medicinal value. Predicting the effects of climate change on the distribution of Z. spinosa is of great significance for the investigation, protection, and exploitation of this germplasm resource. For this study, optimized maximum entropy models were employed to predict the distribution patterns and changes of its present (1970–2000) and future (2050s, 2070s, and 2090s) potential suitable regions in China under multiple climate scenarios (SSP1‐2.6, SSP2‐4.5, SSP3‐7.0 & SSP5‐8.5). The results revealed that the total area of the present potential suitable region for Z. spinosa is 162.60 × 104 km2, which accounts for 16.94% of China's territory. Within this area, the regions having low, medium, and high suitability were 80.14 × 104 km2, 81.50 × 104 km2, and 0.96 × 104 km2, respectively, with the high suitability regions being distributed primarily in Shanxi, Hebei, and Beijing Provinces. Except for SSP‐1‐2.6‐2070s, SSP‐5‐8.5‐2070s, and SSP‐5‐8.5‐2090s, the suitable areas for Z. spinosa in the future increased to different degrees. Meanwhile, considering the distribution of Z. spinosa during different periods and under different climate scenarios, our study predicted that the low impact areas of Z. spinosa were mainly restricted to Shanxi, Shaanxi, Ningxia, Gansu, Liaoning, Inner Mongolia, and Jilin Provinces. The results of core distributional shifts showed that, except for SSP1‐2.6, the center of the potential suitable region of Z. spinosa exhibited a trend of gradually shifting to the northwest.